Stratification of methotrexate‐induced oral ulcers in rheumatoid arthritis patients. (8th February 2021) - Magdy, Eman; Ali, Shereen
Abstract: Aim: There is a deficiency in the data concerning the clinical forms of methotrexate‐induced oral ulcers. This study was conducted to stratify clinical forms of methotrexate‐induced oral ulcers in rheumatoid arthritis patients. Methods: This study included rheumatoid arthritis patients receiving methotrexate as monotherapy. All eligible patients were subjected to thorough clinical examination and full history to identify oral events. Drug history, dose, and duration of MTX were recorded. Results: Among 794 rheumatoid arthritis patients, mean methotrexate dose and duration were 14.3 mg/week and 5.2 years, respectively. Oral ulcers were detected in 6.2% of the patients and 30% of the patients reported previous oral ulcers. Among the detected oral ulcers, 44.9% manifested as deep irregular ulcers, 30.6% presented as aphthous‐like ulcers, 14.3% were diffuse mucositis, and 10.2% appeared as lichenoid reaction. Conclusion: Methotrexate‐induced oral ulceration could be localized or generalized. Localized forms were more noticed than generalized forms. Higher doses and longer durations of methotrexate were detected among patients with generalized oral ulcers.